Relationships between selected parameters of pelvis in children and adolescents aged 3-20 years of age in the context of gender and environment - Mirosław Mrozkowiak (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
Introduction: Pelvis is a part of the skeletal system. It is a pelvic ring composed of the sacral bone, coccygeal bone and two pelvic bones, the right one and the left one. When walking, pelvis undergoes angular displacement in the frontal, sagittal and transverse planes. Material and methods: The studies were conducted in randomly selected kindergartens and schools from the urban and rural environment in the Warmia and Masuria region and the Pomerania region among 1832 male and 1974 female subjects at the age of 3 - 20 years. The photogrammetric method was applied to diagnose the angle of pelvic torsion to the left and to the right side in the frontal plane. Results: The general analysis of the correlation coefficient including positive and negative correlations suggested that the values ranged between 0.43 and 0.44 for KNM and KNM-, from -0.1 to 0.1 for KNM and KSM-, and from -0.08 to -0.04 for KNM and KSM. Spearman's rank correlation coefficient for KNM- and KSM- ranged between -0.11 and -0.1, for KNM and KSM from -0.14 to 0.11, and for KSM- and KSM -0.72 to -0.7. Conclusions: A high degree of negative correlations was recorded between the angle of pelvic torsion in the transverse plane to the left and the angle of pelvis twisted to the right side. A poor degree of positive correlation was observed between the parameters of KNM and KSM- as well as KNM- and KSM. A poor negative correlation was reported between the parameters of KNM and KSM and the parameters of KNM- and KSM-. The correction procedure for the pelvic position should consider mutual interdependencies of tilt angles in the frontal plane and of torsion angles in the transverse plane.